Lepton and Photon Interactions at High Energies 2000
DOI: 10.1142/9789812793942_0026
|View full text |Cite
|
Sign up to set email alerts
|

Structure Functions in Deep Inelastic Lepton-Nucleon Scattering

Abstract: Latest results on structure functions, as available at the Lepton-Photon Symposium 1999, are presented. This report focusses on three experimental areas: new structure function measurements, in particular from HERA at low x and high Q 2 ; results on light and heavy flavour densities; determinations of the gluon distribution and of α s . As the talk was delivered at a historic moment and place, a few remarks were added recalling the exciting past and looking into the promising future of deep inelastic scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…As expected even with our calculation it is found that is found to be larger than 2 . It is mainly due to the gluon emission as predicted earlier [8]. However although theoretical calculation predict a negative value for low Q 2 region as the result got by our model too, a negative value of may not be measured.…”
Section: Resultssupporting
confidence: 47%
“…As expected even with our calculation it is found that is found to be larger than 2 . It is mainly due to the gluon emission as predicted earlier [8]. However although theoretical calculation predict a negative value for low Q 2 region as the result got by our model too, a negative value of may not be measured.…”
Section: Resultssupporting
confidence: 47%
“…The success of fixed-order perturbative QCD in describing the increasingly precise HERA F 2 data when Q 2 1 GeV 2 has been confirmed many times by successful NLO fits [24]. From these a gluon distribution may be extracted, (see figure 3(a)), and predictions for F c 2 (figure 3(b)), dijet production, and F L , all of which have now been supported by direct measurements [25]. Clearly fixed-order perturbative QCD works well at HERA: none of these predictions is trivial, and all are successful.…”
Section: Qcd: Resummation Of Logs Of Qmentioning
confidence: 76%
“…If one were to insist on such a hard-pomeron singularity, one would thus, to be consistent, also have to argue that NLO perturbative QCD could not be applied in this region. The many quantitative successes of NLO perturbative QCD at HERA [4,24,25] would then have to be considered merely fortuitous. Conversely, if one instead accepts that the success of the perturbative predictions is significant, one would then have to conclude that the simple assumption (3) that the rightmost singularity in the j -plane is a simple pole is incorrect, since the perturbative results rely for their success on a soft input.…”
Section: Qcd: Resummation Of Logs Of Qmentioning
confidence: 99%